2014
DOI: 10.1142/s1793431114500092
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Industrial Sheds and Liquefaction Effects During May 2012 Emilia Earthquakes Sequence in Northern Italy

Abstract: On May 20, 2012 at 2:03 UTC, a Mw 6.1 earthquake occurred in Emilia Region of Northern Italy. The event was preceded by a Ml 4.1 foreshock on May 19, 2012 at 23:13 UTC, and followed by several aftershocks, twenty of them with a magnitude Mw greater than 4. The epicentral area of the seismic sequence covers alluvial lowland that is occupied by both agricultural and urbanized areas. Liquefaction effects were observed in several villages on the west side of Ferrara which were built upon former river beds such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The overall damage to residential buildings was minor, but damage was particularly evident for old and poorly maintained masonry structures. On the other hand, significant damage to industrial facilities was observed (Cimellaro et al, 2014).…”
Section: The 2012 Emilia Seismic Sequence and Observed Liquefaction Pmentioning
confidence: 99%
“…The overall damage to residential buildings was minor, but damage was particularly evident for old and poorly maintained masonry structures. On the other hand, significant damage to industrial facilities was observed (Cimellaro et al, 2014).…”
Section: The 2012 Emilia Seismic Sequence and Observed Liquefaction Pmentioning
confidence: 99%
“…The risk posed by geological hazards seems to be poorly understood, even in the highly industrialized and populated Northern Italy, as illustrated for instance by the "expected" extensive damage to modern industrial buildings during the May-June 2012 seismic sequence in the Po Plain (e.g., Dolce and Di Bucci, 2014;Cimellaro et al, 2014;Michetti et al, 2012), resulting in losses totaling over 13 billion euros (Daniell and Vervaeck, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…IEEE Standard 693 focuses purely on requirements and certification of seismic hazard compliant substation equipment [16]. Additionally, there are numerous reconnaissance reports on earthquake impacts to electricity systems, particularly through databases such as the Multidisciplinary Center for Earthquake Engineering Research (MCEER) at the University of Buffalo [6,[17][18][19][20][21][22][23]. Much of this work focuses on the impact to an individual component of a substation or aggregates expected component damage to estimate damage to a substation.…”
Section: Introductionmentioning
confidence: 99%